1978
DOI: 10.1029/ja083ia09p04359
|View full text |Cite
|
Sign up to set email alerts
|

On the role of steepened structures and drift waves in equatorial spread F

Abstract: A time domain analysis, performed upon electron density data obtained on the bottomside of the F peak during equatorial spread F conditions, indicates that the observed k -2 wave number spectrum is due to sharp gradients in the medium and not to plasma turbulence. The gradients are then shown to be unstable to drift waves with a peak growth rate of about 1 s -• which occurs at perpendicular wavelengths near the ion gyroradius. These waves may be responsible for some of the intense backscatter detected by VHF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 28 publications
5
71
0
Order By: Relevance
“…(To convert from seconds to kilometers, multiply by 2.) The rocket probes detected intense irregularities on the bottomside of the equatorial F region [Costa and Kelley, 1978] which had structure very similar in appearance to the barium cloud data. In addition, both sets of' data have nearly identical power spectra not only in spectral form but absolute value.…”
Section: Comparison Of Experiments and Theorymentioning
confidence: 70%
“…(To convert from seconds to kilometers, multiply by 2.) The rocket probes detected intense irregularities on the bottomside of the equatorial F region [Costa and Kelley, 1978] which had structure very similar in appearance to the barium cloud data. In addition, both sets of' data have nearly identical power spectra not only in spectral form but absolute value.…”
Section: Comparison Of Experiments and Theorymentioning
confidence: 70%
“…During the rocket flight, which occurred subsequent to the 11 cm radar backscatter measurements, in situ probes detected sharp density gradients (L n P 45m; Kelley, private communication, 1980) and large density depletions (n e ~ several x 10 4 cm-3 ; E. Szuszczewicz, private communication, 1980) at high altitude (-500 km). We note that previous in situ rocket measurements have found density gradient scale lengths as small as 30m (Costa and Kelley, 1978a).…”
Section: Discussionmentioning
confidence: 99%
“…Woodman and LaHoz (1976) ®rst identi®ed valley region irregularities below the main plumes in the RTI radar maps obtained from Jicamarca. Vickrey et al (1984) studied electron density irregularities observed in the F region valley, which were obtained from ®xed bias LP¯own on two rockets launched from Natal, Brazil (Kelley et al, 1976(Kelley et al, , 1979Costa and Kelley, 1978) and from Kwajalein Atoll (Szuszczewicz et al, 1980Rino et al, 1981;Kelley et al, 1982b). During these twō ights quasi-sinusoidal¯uctuations in the F region valley (170 to 200 km) were observed where the local zero order vertical plasma density gradient nearly vanishes.…”
Section: Intermediate Scale Irregularitiesmentioning
confidence: 99%
“…Similar k )2 power law scaling was observed by Dyson et al (1974) using AE satellite data, by Morse et al (1977) in the Equion experiment and also by Kelley and Mozer (1972) using the electric ®eld data. Costa and Kelley (1978) found that sharp density gradients (gradient scale length, L < 100 m) could de-stabilize collisional drift waves. Rino et al (1981) discussed the ®xed-bias Langmuir probe derived electron density power spectra, obtained from Plumex-I rocket, launched from Kwajalein Atoll (9.4°N, 167.45°E).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation